Handbook on modular coordination general principles, rules, applications. (Makati, M.M. Philippine Domestic Construction Board, 1992)
Offers a practical guide to modular coordination. The work provides basic information, modules and reference systems, design rules and conventions, sample plans and a list of reference materials. It is designed for reference by people with background in building design and construction.
Keywords: Modular coordination (Architecture) -- Handbooks, manuals, etc; Building materials -- Standards